AQUEOUS - ORGANIC PHASES SEPARATION BY MEMBRANE REACTORS IN BIODESULFURIZATION REACTIONS - Claudia Berdugo; Rocío Caballero; Rubén-Darío Godoy (CT&F Ciencia, Tecnología & Futuro, 2002)
This work presents a membrane bioreactor prototype used to separate emulsion phases formed in the biodesulfurization reaction. Hydrophobic membranes used for the construction of the prototype allow the separation of the organic/watery phases. The separation unit resembles a tube and carcass heat exchanger. By feeding the emulsion through the housing and due to the pressure gradient pushed on the membrane, the organic phase pass through and allow to obtain an organic phase free of cells and water. Several organic phase/watery phase ratios and many cellular concentrations were evaluated. Results indicate that is possible to separate the phases by manipulating the fluid pressure within the bioreactor. This is possible even for cellular concentrations of the order of 7 g/l. The system can also be used as a reaction unit. The biological conversion was evaluated by verifying the presence of 2-HBP, one of the metabolites of the path 4S in the biodesulfurization reaction. This bioreactor configuration has not been explored before for the biodesulfurization process and therefore it represents an innovation in this research area. En este trabajo se presenta un prototipo de biorreactor de membranas para la separación de las fases de la emulsión formada en la reacción de biodesulfurización. Las membranas hidrofóbicas utilizadas para la construcción del prototipo permiten la separación de las fases acuosa orgánica. La unidad de separación se asemeja a un intercambiador de tubo y coraza. Alimentando la emulsión por la carcasa y gracias al gradiente de presión que se ejerce sobre la membrana, la fase orgánica permea la membrana permitiendo la obtención de la fase orgánica libre de células y agua. Se evaluaron diferentes relaciones fase orgánica/ fase acuosa y diferentes concentraciones celulares. Los resultados indican que es posible separar las fases manipulando la presión del fluido al interior del biorreactor incluso a concentraciones celulares del orden de 7 g/l . El sistema puede ser utilizado también como unidad de reacción, la conversión biológica se evaluó verificando la presencia de 2-HBP, uno de los metabolitos de la ruta 4S en la reacción de Biodesulfurización. Esta configuración de biorreactor no ha sido explorada antes para el proceso de biodesulfurización y por tanto representa una innovación en el área.